Intestinal parasitism in preschool and school students treated in the EsSalud Medical Center of Celendín, Cajamarca - Morales Del Pino, Jimmy Rinaldo (2016)
Objective: To determine the prevalence of parasitic infections in preschool and school children of Celendín district, treated at the EsSalud medical center and find the presence of parasitic subtypes. Material and methods: Observational, descriptive, cross-sectional research, conducted between July 2015 and January 2016 in the clinical laboratory service of EsSalud Medical Center of Celendín, Cajamarca. A data collection sheet was used for each participant to collect clinical data, demographic data and personal interaction. Parasitological samples of 96 children were processed by using direct examination, test of Graham and spontaneous sedimentation technique. Univariate analysis was used to find frequencies, percentages and standard deviations, and for the bivariate analysis we used Chi-square and Fisher's exact tests to associate the degree of parasitism with each variable obtained. Results: The prevalence was 90.6% (87/96). Blastocystis hominis 81.2%, iodamoeba bütschlii 6.3%, Endolimax nana 19.8%, Entamoeba coli 35.4%, Chilomastix mesnilii 13.5%, Giardia lamblia 9.4%, Enterobius vermicularis 16.7% was found and Ascaris lumbricoides 1.0%. 20.8% (20/96) of the participants had similar structures to Urbanorum spp. Multiparasitism predominated (60.4%) and there was a statistically significant association between the level of education and parasitical degree (p = 0.017). Conclusions: There was a high prevalence of parasitic infections in children in preschool and school age of Celendín district attended at the EsSalud medical center being Blastocystis hominis parasite the most predominant.